A study on gap between prior job expectation and actual working condition in international semiconductor companies Melaka / Syazwani Kamarulzaman - Kamarulzaman, Syazwani (2015)
College or university graduates come into the workplace with expectations that they will obtain satisfied, secure and well-paying employment (Shelley, 1994) mainly based on what they have been taught in their formal education. The aim of this research is to attempt to reveal the difference between what fresh graduates expect and their actual experiences pertaining to the working environment. Besides that it also to identify which factors is the most significant factor for actual working condition with organizational culture, motivation, communication and team work. Hence, this research used primary and secondary data in collection the data as data method. As for the interpretation data, the researcher used correlation coefficient for testing hypothesis, while regression analysis for testing the most significant variables in this research. Using a set of self-administered questionnaires, data were collected from 80 graduates. They were asked to indicate their preference on organizational culture, motivation, communication and team work. Using the same dimensions, the respondents then reported their actual experiences, thus enabling gaps to be determined. Based on the research findings, the factor of organizational culture, motivation, communication and team work have positive correlation with the actual working condition. Then, the motivation factor and team work have significant relationship with actual working condition. While organizational culture and communication are not at level of significant. The results from paired-sample t-tests suggest that there is no significant expectation gaps exist in all the areas surveyed. Lastly, the most significant variable is team work.